Iraq’s Perception of Kuwaiti Foreign Policy Decision-Making after 2003 " - Al-Jourani , Haider Sobkhi Afat (Tikrit Journal For Political Science, 2017)
Kuwait is significant to Iraq due to its association with the events of 1990/1991 and 2003, both of which had a negative impact on Iraq and its circumstances throughout the preceding period. One of the crucial points that necessitates examination and study is the Kuwaiti perspective towards Iraq, which shapes Kuwait's foreign policy towards Iraq. This is the subject matter addressed in this research. After 2003, Iraq started to perceive the Kuwaiti foreign policy decision-maker and its influence on the bilateral relations between the two countries. There was an increasing focus on developing shared interests in politics, economy, security, and culture. Diplomatic relations between Iraq and Kuwait were restored, and official visits between officials of both countries were exchanged. Pending issues between Iraq and Kuwait, such as borders, outstanding debts, and war reparations, were addressed, and agreements and understanding solutions were reached between the two nations.